2016
DOI: 10.1007/s11104-016-2945-7
|View full text |Cite
|
Sign up to set email alerts
|

Global proteomic mapping of alkali stress regulated molecular networks in Helianthus tuberosus L.

Abstract: Background and aims Soil salinization with high pH condition is a major abiotic stress to plant growth and crop productivity. Helianthus tuberosus L. is an important stress tolerant plant and can survive in the salinealkali soil and semiarid areas. The aim of this study is to identify the effect of alkali stress on H. tuberosus through global proteomics analysis and improve understanding of the alkalinity resistance of plants. Methods H. tuberosus seedlings were exposed to different level alkali stress for 7 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 75 publications
1
8
1
Order By: Relevance
“…In this study, the RPs decreased in both non‐AM seedlings under AS (AS vs. CK analysis) and AMF seedlings under AS (AS‐AM vs. AM analysis), indicating that protein synthesis was affected by AS (Tables S2 and S3). Similar results were also found in Helianthus tuberosus by Zhang et al (). Interestingly, we also found that eight small‐subunit and 22 large‐subunit RPs were up‐regulated after AMF inoculation under AS (AS‐AM vs. AS analysis; Table S5 and Figure ).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In this study, the RPs decreased in both non‐AM seedlings under AS (AS vs. CK analysis) and AMF seedlings under AS (AS‐AM vs. AM analysis), indicating that protein synthesis was affected by AS (Tables S2 and S3). Similar results were also found in Helianthus tuberosus by Zhang et al (). Interestingly, we also found that eight small‐subunit and 22 large‐subunit RPs were up‐regulated after AMF inoculation under AS (AS‐AM vs. AS analysis; Table S5 and Figure ).…”
Section: Discussionsupporting
confidence: 90%
“…Salt‐alkaline soil is one of the major abiotic constraints that limit plant distribution and yield, and this soil will cover >50% of arable lands throughout the world by 2050 (Yu, Chen, Wang, Sun, & Dai, ; Zhang et al, ). In the northeast of China, alkaline meadows cover >70% of the land, and the area continues to expand (Lin, Wang, Sun, Mu, & Yan, ).…”
Section: Introductionmentioning
confidence: 99%
“…The core of the OEC is the combination of Mn cluster in Ca 2+ and Cl -, so Clplays an important role in stabilizing OEC functions. In this study, the activity of OEC on the donor side of PSII did not decrease significantly under NaCl stress, which may be related to the role of Cl - (Pang et al, 2010;Zhang et al, 2016b). However, under NaHCO3 stress, except for the significant increase of PPD4 expression, the expressions of other related proteins in the PSII donor side were significantly decreased compared with CK.…”
Section: .Discussion 31 Response Of Photosynthesis and Related Protcontrasting
confidence: 51%
“…The increase in relative variable fluorescence ( V K ) value at point K (0.3 ms) is considered as the specific marker for inhibition of activity at PSII electron donor side, especially the activity of oxygen evolution complex (OEC) (Jiang et al, 2008; Zhang et al, 2012). The increase in relative variable fluorescence ( V J ) at point J (2 ms) indicates that the electron transfer from Q A to Q B is blocked and there is accumulation of reduced Q A (Haldimann and Strasser, 1999, Zhang A.Q. et al, 2016; Zhang H.H.…”
Section: Discussionmentioning
confidence: 99%